Jarid2 coordinates nanog expression and PCP/Wnt signaling required for efficient ESC differentiation and early embryo development - Landeira,D; Bagci,H; Malinowski,AR; Brown,KE; Soza-Ried,J; Feytout,A; Webster,Z; Ndjetehe,E; Cantone,I; Asenjo,HG; Brockdorff,N; Carroll,T; et al. (Cell Reports, 2015)
Jarid2 is part of the Polycomb Repressor complex 2 (PRC2) responsible for genome-wide H3K27me3 deposition. Unlike other PRC2-deficient embryonic stem cells (ESCs), however, Jarid2-deficient ESCs show a severe differentiation block, altered colony morphology, and distinctive patterns of deregulated gene expression. Here, we show that Jarid2−/− ESCs express constitutively high levels of Nanog but reduced PCP signaling components Wnt9a, Prickle1, and Fzd2 and lowered β-catenin activity. Depletion of Wnt9a/Prickle1/Fzd2 from wild-type ESCs or overexpression of Nanog largely phenocopies these cellular defects. Co-culture of Jarid2−/− with wild-type ESCs restores variable Nanog expression and β-catenin activity and can partially rescue the differentiation block of mutant cells. In addition, we show that ESCs lacking Jarid2 or Wnt9a/Prickle1/Fzd2 or overexpressing Nanog induce multiple ICM formation when injected into normal E3.5 blastocysts. These data describe a previously unrecognized role for Jarid2 in regulating a core pluripotency and Wnt/PCP signaling circuit that is important for ESC differentiation and for pre-implantation development.